(untitled) (Jurnal Pelita Pendidikan, 2016)
This research was carried out to find out The Implementation of Group Investigation Model on Learning Outcomes at The Topic Ecosystem Class X in SMA Negeri 11 Medan Academic Year 2014/2015. Therefore, an experimental research was carried as the research as a research design. The population was 2014/2015 academic years students, in the second years students of SMAN 11 Medan, especially the students of class X which consisted of 320 students. From the population was taken 80 students as the sample by using Random Sampling. They were divided into two groups, 40 students in experimental groups taught by using group investigation model and 40 students in control group taught by using direct instruction. Based on the result of research obtained the mean pretest in class control 44.8 and experimental class 51.7, this shows the initial ability of the both classes is same similarity. Then the both of classes were given a different treatment, the experimental class used Group Investigation and control class used Direct Instruction. After the learning had finished, the both of classes given posttest of control class 77.9 and experimental class 81.75.The result test t obtained that t count > t table (2.03 < 1.66) then H0 is rejected and Ha accepted. Furthermore, based on percentage of students activity showed that students in experimental class more active than class control. It can be conclude that is effect of group investigation learning outcomes on students at topic ecosystem in class X SMA Negeri 11 Medan Academic Year 2014/2015. Key words: group investigation model, learning outcome, activity